The Accuracy of Economical Statistical Data - Valkauskas, Romualdas (Ekonomika, 1996)
Economical statistics consists of micro and macrostatistics. Here basic is economical and statistical count. The Accuracy of the count is a very important problem for science and the practice of statistics. We separate this problem into two cases: accuracy of the count in microeconomics and accuracy of the count in macroeconomics. In the count of microeconomics, a very important problem is which a basis make separate the form and the grade of accuracy. In the basis of the situation lies a collection fort statistics. This collection is made op of the numbers: 3; 2.5; 2; 1.5; 1, and 0.5. In the count of macroeconomics a grade accuracy of economical size is very important. For example, the accuracy of the size of national resoorces. Research numbers of the resoorces of Lithuania show that the accuracy can be about +6.665%.